Solvency and fixed assets financing of agriculture, forestry and fishing sector in the Republic of Serbia - Jasmina Bogićević; Nemanja Karapavlović; Biljana Jovković (Economic Themes, 2021)
This paper aims to examine solvency and fixed assets financing of Agriculture, Forestry and Fishing sector (Sector A) in the Republic of Serbia. We also examine whether there is a difference between this Sector's enterprises and entrepreneurs regarding these two aspects of their financial position. The research is based on the Financial Statements Annual Bulletins available on the official website of the Serbian Business Registers Agency. The period of six consecutive years is covered (2013 - 2018). Solvency and fixed assets financing were analyzed separately for Sector A enterprises and entrepreneurs. Standard ratio indicators were used to determine these relevant aspects of financial position. The conducted analysis showed differences between this Sector's enterprises and entrepreneurs regarding the solvency. The research results revealed that, despite a slight improvement in certain solvency indicators, entrepreneurs were insolvent during the observed period. The fixed assets financing indicators showed that the lack of equity for new investments financing was compensated mainly by long-term borrowing at enterprises' level and by short-term borrowed sources at entrepreneurs' level.
Keywords: M41; O13; Q12; Q22; Q23; 330; agriculture; forestry and fishing sector; solvency; fixed assetsfinancing; enterprises; entrepreneurs